Exploring symbolism and questioning meanings to discover diverse poetic perspectives:'Halaj Al-Nihayat' collection by the poet Abdelhakem Bellahya as an exemplary model (مجلة إحالات, 2026)
The modern poetic discourse aims to construct a distinctive aesthetics that sets it apart from theinherited classical poetic traditions, which have become entrenched as previous experiences in thehistory of Arab reception. Modern poetic writing diverges from the conventional by rushing to create new stylistic elements, intending to break the reader's expectations and build a fresh interpretation ofpoetic texts. As a result, modern poets have opened the door to extensive poetic experimentation, seekingpoetic characteristics that embody the temporal specificities to which they belong. This involves posingnew questions related to the contemporary world and its psychological crises. The collection 'Halaj AlNihayat' is one of the experiments that embarked on the adventure of this poetic experimentation, attempting to surpass prevailing norms and establish new perspectives on existence, humanity, and the world.